37th Winter School on Wave and Quantum Acoustics - Roman BUKOWSKI (Archives of Acoustics)
I have a great pleasure to give the "Archives of Acoustics" Readers possibility acquaint with topics presented at 37th Winter School on Wave and Quantum Acoustics. This School, organized by Upper Silesian Division of the Polish Acoustical Society and Institute of Physics at Silesian University of Technology, is planned at the end of February 2008 in beautiful scenery of Wisła, the center of rest in Silesian Beskidy Mountains. As always, the School has been a place where achievements of various sections of acoustics are being exchanged. Specially interested topics are: molecular acoustics, quantum acoustics, acousto-optics, magnetoacoustics, acoustoelectronics, photoacoustics, acoustics of solids etc. Moreover, some similar and related topics, for example optoelectronics and thermal wave methods, will be presented~too. Traditionally the School will be divided on three different, but complementary, parts -- Winter Workshops (WW). Chronologically it will be: 4th WW on Acoustoelectronics and Optoelectronics (chairman prof. Tadeusz Pustelny), 4th WW on Molecular Acoustics, Relaxation and Calorimetric Methods (chairwoman dr Marzena Dzida) and 13th WW on Photoacoustics and Thermal Waves Methods (chairman prof. Jerzy Bodzenta). This dividing was very well accepted by Participants. After acceptation by revievers the School lectures will be published in one of two journals -- in European Physical Journal -- Special Topics (which is published by EDP Sciences and covered in the ISI database as continuation of Journal de Physique IV) or in Journal of Molecular and Quantum Acoustics (annual journal published by Upper Silesian Division of the Polish Acoustical Society). Once again we have taken pains to organize this conference taking into account the fact that it is an important event for acousticians, opticians and other Polish and foreign scientists. We hope that this reach conference program will gain acceptance and respect among its potential participants. We count on your numerous response and active participation.